Fabrication of three-dimentional triarylmethane polymers derivatives as efficient counter electrodes for dye-sensitized solar cells. (10th March 2022) - Qian, Junning; Lu, Qingyi; Xu, Feng; He, Guohang; Xia, Jiangbin
Abstract: Through rational molecular design, two kinds of triarylmethane compounds of tris(2, 3-dihydrothieno[3, 4- b ][1, 4]dioxin-5-yl)methane (TDM) and tri(1H-pyrrol-2-yl)methane (TPM) are successfully synthesized, and they are further made into counter electrode (CE) by facial chemical polymerization method. The as-prepared three-dimentional (3D) PTDM nanosphere exhibits excellent electrocatalytic performance as CE towards triiodide reduction reaction (TRR) in dye-sensitized solar cells (DSCs). Particularly, the outstanding photovoltaic device prepared with 3D PTDM material realizes a high power conversion efficiency (PCE) as 8.34%, which is better than Pt (7.90%) and PTPM (4.15%). The success of PTDM further reveals that a rational molecular design is crucial for the sustainable development of high efficiency electrocatalytic counter electrode material in DSCs. Graphical abstract: Image, graphical abstract .